2020
DOI: 10.3390/cancers12020465
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CDKN1A mRNA and Protein Expression Are Independent Predictors of Poor Outcome in Chromophobe Renal Cell Carcinoma Patients

Abstract: Chromophobe renal cell carcinoma (chRCC) patients have good prognosis. Only 5%–10% patients die of metastatic disease after tumorectomy, but tumor progression cannot be predicted by histopathological parameters alone. chRCC are characterized by losses of many chromosomes, whereas gene mutations are rare. In this study, we aim at identifying genes indicating chRCC progression. A bioinformatic approach was used to correlate chromosomal loss and mRNA expression from 15287 genes from The Cancer Genome Atlas (TCGA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 59 publications
(89 reference statements)
0
15
0
Order By: Relevance
“…So, it is worthy of additional studies on SNCAIP function and potentially drug development in ccRCC. We also identified CDKN1A alterations in the metastatic groups, and loss of CDKN1A had been proved to be an unfavorable predictor of prognosis in chromophobe renal cell carcinoma patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…So, it is worthy of additional studies on SNCAIP function and potentially drug development in ccRCC. We also identified CDKN1A alterations in the metastatic groups, and loss of CDKN1A had been proved to be an unfavorable predictor of prognosis in chromophobe renal cell carcinoma patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…P21, also known as CDKN1A which resided in 6p21.2 20,21 , has been investigated involvement in cell cycle regulation, differentiation, cell migration, cytoskeletal dynamic, apoptosis, transcription, DNA repair, induction of totipotent stem cells, autophagy and senescence 22,23 . Commonly accepted is that P21 as a member of cyclin-dependent kinase inhibitors (CDKI) interacts with various cell cycle proteins to mediate G1/S growth phase arrest in response to different stimuli 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…CDKN1A, which resides in 6p21.2, is affected by frequent loss of one chromosome 6 allele in chromophobe RCC. 53 Analysis of TCGA data of chromophobe RCC demonstrated that loss of one CDKN1A allele was closely linked to lower CDKN1A mRNA expression levels. It has been recently shown that decreased CDKN1A expression at mRNA and protein levels were associated with short overall survival and were independent predictors of prognosis in chromophobe RCC.…”
Section: Molecular Studies and The 'Cell Of Origin' Theorymentioning
confidence: 99%